Quality assessment of aged mineral oil-synthetic ester retrofilled transformer oil through total acid number and fourier transform infrared spectroscopy - Zainuddin, Hidayat; Othman, Nur Amirah; Yahaya, Muhammad Sharil; Azis, Norhafiz; Ibrahim, Zulkifli; Che Musni, Mohd Affendi (School of Electrical Engineering and Informatics, 2023)
The retrofilling process involves the substitution of mineral oil in an existing transformer with ester oil serves as an alternate method to prolong the transformer lifetime. This pertains to the excellent characteristics of ester oil, recognized for its moisture resilience which in turns imparts a unique advantage by extending the lifespan of insulation paper. Nevertheless, the retrofilling procedure involves mixing the new ester oil with the existing aged mineral oil (AMO) in the transformer oil, which ultimately impacts the performance of the new ester oil. Hence, it is crucial to evaluate the performance of mixed oil to identify any indications of oil deterioration due to retrofilling before energising the transformer. In evaluating the performance of aged mineral-synthetic ester (AMO/SE) retrofilled oil, this work presents the analysis of the total acid number (TAN) and Fourier Transform Infrared (FTIR) spectra. Prior to the retrofilling process using fresh-treated synthetic ester oil, four distinct amounts of aged mineral oil (AMO) were prepared, comprising 3 %, 5 %, 7 % and 9 %. This option provides the opportunity to simulate varying levels of remaining mineral oil present in the transformer. The AMO samples were prepared by subjecting the fresh mineral oil to thermal ageing in a vacuum oven at a temperature of 130 ℃ for two different durations, i.e. 75 and 150 hours. Throughout the collected data, the amount of acids in AMO/SE oil has exhibited a rising trend with a decreased in proportions of AMO in the fresh-treated synthetic ester oil for both AMO conditions. Meanwhile, the severity of AMO conditions give a significant effect to the acid growth in AMO/SE retrofilled oil. In conjunction with FTIR spectra, the rise in acid concentration in retrofilled AMO/SE oils was clearly observable in the C=O stretch in the region of 1710-1770 cm−1, which exhibited a significant association with the TAN value.